2017
DOI: 10.3987/com-16-s(s)68
|View full text |Cite
|
Sign up to set email alerts
|

An Enantioselective Synthesis of 2-Imidazolidinones through Bifunctional Thiourea-Catalyzed Tandem Mannich/Cyclization of Isocyanatomalonate Diester

Abstract: A chiral bifunctional thiourea-catalyzed Mannich reaction of diethyl 2-isocyanatomalonate with N-sulfonylimines was described. The tandem cyclization proceeded smoothly after Mannch reaction, directly furnishing chiral 2-imidazolidinones in 72-99% yields with 83-98% ees. Sterically demanding sulfonyl group was crucial for aliphatic imines to afford the corresponding product in high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In 2014, Takemoto's group reported the asymmetric aldol reaction of 2‐isocyanatomalonate esters with aldehydes in the presence of a thiourea catalyst, [10] and then our group has used this strategy to the asymmetric synthesis of amphenicol antibiotics [11] . Subsequently, the [3+2] cyclization reaction of 2‐isocyanatomalonate esters with aldimines via the cinchona alkaloid‐derived catalyst was developed by Takemoto's group [12] . Later on, Pedro's group found that the reaction of 2‐isocyanatomalonate esters with unsaturated alkenes could give substituted chiral γ‐lactams using the Mg(OTf) 2 −BOX complex [13] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Takemoto's group reported the asymmetric aldol reaction of 2‐isocyanatomalonate esters with aldehydes in the presence of a thiourea catalyst, [10] and then our group has used this strategy to the asymmetric synthesis of amphenicol antibiotics [11] . Subsequently, the [3+2] cyclization reaction of 2‐isocyanatomalonate esters with aldimines via the cinchona alkaloid‐derived catalyst was developed by Takemoto's group [12] . Later on, Pedro's group found that the reaction of 2‐isocyanatomalonate esters with unsaturated alkenes could give substituted chiral γ‐lactams using the Mg(OTf) 2 −BOX complex [13] .…”
Section: Figurementioning
confidence: 99%
“…[11] Subsequently, the [3 + 2] cyclization reaction of 2isocyanatomalonate esters with aldimines via the cinchona alkaloid-derived catalyst was developed by Takemoto's group. [12] Later on, Pedro's group found that the reaction of 2-isocyanatomalonate esters with unsaturated alkenes could give substituted chiral γlactams using the Mg(OTf) 2 À BOX complex. [13] However, the types of electrophiles used in these reactions have remained largely unexplored.…”
mentioning
confidence: 99%
“…It has been reported to react with several electrophiles via asymmetric cycloaddition reactions to construct five-membered nitrogen-containing heterocycles (Scheme 2b). 11–13 In 2014, Takemoto's group disclosed the thiourea-catalyzed asymmetric formal [3 + 2] cycloadddition reaction of 2-isocyanatomalonate diester with various aldehyde compounds for the first total synthesis of mycestericin C, 11 a , b and then our group successfully applied this strategy for the asymmetric synthesis of amphenicol antibiotics and chiral spirooxazolidinone oxindole. 12 Subsequently, a chiral bifunctional thiourea-catalyzed Mannich/cyclization cascade reaction of 2-isocyanatomalonate diester with imine compounds was reported by Takemoto's group.…”
mentioning
confidence: 99%